Occurrence of Minervarya asmati (Howlader, 2011): A New Distribution Record of Meghalaya, Northeast India - Das, Avishek; Shylla, Treferous; Hmar, Esther L.; Shangpliang, P. Wankitlang; Adhikari, Samrat; Lyngdoh, Dominic; Dorphang, Mebari Vanessa R.; Rangad, Duwaki; Tron, Ronald Kupar L.; Ranee, Graham Bakynson (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Bangladeshi Cricket Frog (Minervarya asmati), previously recorded in Bangladesh, Manipur, and Mizoram, is newly reported from Shillong and Cherrapunjee, Meghalaya, India. During a herpetological survey in March 2024, three male specimens were collected from paddy fields and ephemeral pools. Morphological traits matched existing descriptions, and phylogenetic analysis of 16S rRNA sequences confirmed species identity with 100% bootstrap support. This finding extends the known range northward by 260 km. With M. asmati, Meghalaya’s amphibian diversity reaches 62 species. The study emphasizes the need for further surveys to document amphibian distribution and assess conservation priorities in the region.